PENGARUH PENAMBAHAN ABU SEKAM TERHADAP SIFAT MEKANIK BATU BATA MERAH - Cita Yulianto; Agus Setyawan; Dody Irnawan (JURNAL TEKNOSAINS KODEPENA, 2022)
Brick is a non-structural material that is widely used by the community in building houses in general. There are so many brick craftsmen scattered throughout the province of Central Java, but innovation is needed in the manufacture of these bricks, so research is needed to determine the effect of adding rice husk ash as a mixed material and the length of time for burning bricks on the mechanical properties of bricks in terms of the test. porosity, burn loss, and compressive strength, as well as knowing the percentage of addition of rice husk ash and the best burning time for bricks. This study uses a sample of bricks in the form of blocks with a length of 22.5 cm, a width of 11 cm, and a height of 4 cm and a cube shape with a side size of 5 cm. Variations in the composition of rice husk ash added were 0%, 5%, 10%, and 15%. Making bricks is done by molding a mixture of clay, water and husk ash by compacting, drying for 3 days and burning for 12 hours and 24 hours. Testing of mechanical properties of bricks includes porosity, burn loss, and compressive strength tests. The addition of rice husk ash with a composition percentage of 5% to 15% can affect the mechanical properties of bricks, namely reducing porosity and burning shrinkage and increasing the compressive strength of bricks. The burning time of the bricks also affects the mechanical properties of the bricks. Based on the test results, each of the best test values, namely the minimum porosity value was achieved at the percentage of rice husk ash as much as 5% by burning for 24 hours, namely 18.5%. The minimum burn loss value was achieved at 15% rice husk ash percentage by burning for 12 hours, which was 0.45%. The optimum compressive strength value was achieved at 5% rice husk ash percentage, which was 4.1 N/mm2 by burning for 24 hours.